Assessing the understandability, actionability, and quality of online resources for the self-management of bipolar disorder - Nathan D. Sutera, PharmD; Courtney A. Iuppa, PharmD, BCPP; Leigh Anne Nelson, PharmD, BCPP; Carrie R. Kriz, MS; Nicole A. Gramlich, PharmD, BCPP; Shelby E. Lang, PharmD, BCPP; Ellie S. R. Elliott, PharmD, BCPP; Roger W. Sommi, PharmD, BCPP, FCPP (American Association of Psychiatric Pharmacists, 2022)
Introduction: This study aims to assess the understandability, actionability, and quality of online resources for the self-management (SM) of bipolar spectrum disorders in adults. Methods: An online search using Google, Bing, and Yahoo! search engines was conducted to identify resources for bipolar disorder. Those that were published in English, discussed at least 1 method directed at improving an SM task, and were within the first 25 nonadvertisement results for each search were included. Resources directed specifically at adolescents were excluded. Understandability and actionability of the online resources were evaluated using the Patient Education Materials Assessment Tool (PEMAT). Quality of the online resources was evaluated using the DISCERN instrument. The number of SM tasks each resource discussed was also evaluated. Overall mean appropriateness was calculated by averaging the percentage scores of understandability, actionability, and quality. Results: Fifty-two resources were included. The mean sample scores were 8.4 (SD, 2.1; range, 2-13; maximum, 15) for understandability, 2.2 (SD, 1.2; range, 0-4; maximum, 5) for actionability, and 46.1 (SD, 8.9; range, 30-57; maximum, 75) for quality. The overall mean appropriateness percentage was 53.5% (SD, 11.7%; range, 18%-77%), with a goal of at least 70%. Included resources addressed a mean of 7.1 tasks (SD, 2.5; range, 1-14; maximum, 20). Discussion: Most online resources for the SM of bipolar disorder scored poorly for understandability and actionability based on PEMAT scores and had low to moderate scores for quality using the DISCERN instrument. Future online resources should be designed with the goal of increasing appropriateness for patients.